CONTINUING EDUCATION OF PEOPLE IN POLTAVA AND ITS DEVELOPMENT DURING GERAGOGIKCAL POSTPROFESSIONALIZATION - Звєрєва, В.В.; Зайцев, А.В. (World of Medicine and Biology, 2015)
During the psychological research the effect of continuing education on the success of socialization "third age" is determined. It is shown that the decline of intellectual activity, which is often observed with age, can be prevented through targeted training. Implemented in Ukraine social policy gradually creates conditions for active involvement in the reform process is only the economically active population (18-60 years). This eliminates large socio-demographic group of people, which is in post employment phase. This category of citizens stipulated the passive role of recipient and user social blessings, as well as providing them with protection. Understanding the education elderly that goes from antiquity (the period of the collapse of the slaveholding relations) has not changed in principle to the present. a comparative analysis of the data values and life orientations year olds who are already studying and those who do not have anything to do with is provided. In order to justify the formation of lifelong learning has been applied to study the educational needs gerontogrup. Is developed perspective a work plan for the successful socialization in the society of pensioners. So, education process is perceived as a necessary part of the education system, the accompanying person continuously over a lifetime. Adult education is now treated as a separate industry that is important for social progress.